2016
DOI: 10.1021/acs.nanolett.6b01780
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous, Solvent-Free, Polymer-Templated, Solid–Solid Transformation of Thin Metal Films into Nanoparticles

Abstract: Metal nanoparticles have unusual optical, electronic, sensing, recognition, catalytic, and therapeutic properties. They are expected to form the basis of many of the technological and biological innovations of this century. A prerequisite for future applications using nanoparticles as functional entities is control of the shape, size, and homogeneity of these nanoparticles and of their interparticle spacing and arrangement on surfaces, between electrodes, or in devices. Here, we demonstrate that thin films of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Metal nanoparticles (NPs) have been the subject of increasing interest because of their importance in the field of nanoscience. Gold NPs, in particular, are one of the most widely studied NP systems because of their far-ranging potential applications, such as in catalysis, sensors, optical devices, energy, and biology. However, colloidal Au NPs have high surface energy, and not only readily aggregate but also are difficult to retrieve and reuse in aqueous or nonaqueous media. Therefore, stabilization is essential to immobilize Au NPs and prevent their aggregation in most applications, particularly in catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…Metal nanoparticles (NPs) have been the subject of increasing interest because of their importance in the field of nanoscience. Gold NPs, in particular, are one of the most widely studied NP systems because of their far-ranging potential applications, such as in catalysis, sensors, optical devices, energy, and biology. However, colloidal Au NPs have high surface energy, and not only readily aggregate but also are difficult to retrieve and reuse in aqueous or nonaqueous media. Therefore, stabilization is essential to immobilize Au NPs and prevent their aggregation in most applications, particularly in catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…According to Hernández-Cruz et al, the Au film deposited on FOP material is transformed into nanoparticles over time, resulting in more extensive and more spaced nanoparticles daily [23]. Figures 3 and 4 show the simulation results of the 3D model described in Section 2.2 considering 6, 12, 18, and 24 days of post-deposition time.…”
Section: Simulation Resultsmentioning
confidence: 98%
“…From the wave optics module of COMSOL, the electromagnetic waves-frequency domain and the frequency domain were selected as the physical interface and study type, respectively. The size of the 3D model was varied according to the results reported by Hernández-Cruz et al for 5 nm post-deposited Au films [23]. They reported that the Au layer modifies its morphology very slowly (the process takes more than 20 days), and linear relationships of the width and spacing of the Au nanoclusters versus time were assumed [23].…”
Section: Simulation Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanoparticulate-based drug delivery systems (nano-DDS) have experienced tremendous development and are expected to bring radical solutions to the limitations of conventional chemotherapy 4 , because they improve the tumor accumulation and safety of chemodrugs 5 . Nanomedicines 6 - 8 including liposomes 9 , water-soluble polymers 10 , vesicles 11 , dendrimers 12 , polymer nanoparticles or micelles 13 , 14 , inorganic nanoparticles 15 , and some hybrid organic-inorganic nanosystems 16 , have been studied extensively for this purpose. However, the general outcome of antitumor nanomedicines after past few decades seems far from satisfactory, and one of the reasons seems the inferior delivery efficiency 17 .…”
Section: Introductionmentioning
confidence: 99%